PENYULUHAN TENTANG MANFAAT MINUMAN YOGHURT BAGI TUBUH DI SMP YAPIM BIRU-BIRU - DIAN IKA PERBINA MELIALA; Palas Tarigan; Angga Nugraha Sanjaya (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Counseling about the benefits of drinking yogurt for the body is aimed at studying, developing and applying the science and technology that has been obtained or has been studied by students in lectures to the general public. To find out how to process milk properly so that it produces quality yogurt and is safe for consumption for the body, it is possible to realize the benefits of yogurt so that people are aware of the importance of yogurt for the body, and know how to store yogurt properly.Extension training is carried out using the Planning phase. The planning phase is carried out by forming a PKM Team and then preparing a proposal which will then be submitted. The preparation stage is in the form of making a cooperation agreement with residents in the Blue-Blue area. The socialization stage includes an introduction to the benefits and content contained in milk that can be processed into Yoghurt. good. The teaching stage is carried out by forming small groups of as many as groups consisting of members in each group from the community at Yapim Biru-biru Middle School and then a leader from the group is chosen as the person in charge. The teaching stage aims to provide a theoretical understanding of the target community so that the community is ready to carry out the practice of making quality yogurt. The evaluation stage is carried out to provide solutions to the problems faced by the community in the production process to marketing. This stage is measured through the application of yogurt by the community as well as the increase in community members who produce and cultivate milk as a raw material. The indicator of success at this stage is that solutions to these problems are obtained and become a reference for the future and also continue to develop and run this program. In addition, another indicator of success is the increase in average income in the Blue-Blue area.